Propagação vegetativa de louro-pardo (Cordia trichotoma (Vell.) Arrab. ex Steud.) por estaquia radicular e miniestaquia - Nascimento, Paula Kielse Vargas do (2012)
The aim of this work was to study the vegetative propagation of louro-pardo (Cordia trichotoma (Vell.) Arrab. ex Steud.) from root cuttings and minicuttings. Three trials were conducted. The first trial, roots were gotten from adult trees of louro-pardo. Root cuttings with 5.0 cm of length were classified in two diameters: thick (2.0 - 3.0 cm) and thin (< 2.0 cm). The root cuttings were immersed for 10 s. in an indolbutiric acid (IBA) solution of 0, 4000, 8000 or 12000 mg L-1. At 180 days, the percentages of sprouting and rooting, the number and length of shoots and roots were evaluated. Root cuttings from adult trees of louro-pardo showed 1.25% of sprouting, but they did not root. The second trial, root cuttings were gotten from three year-old plants of louro-pardo and root cuttings classified in small (1.0 - 1.5 cm) and large (1.6 - 2.5 cm) and immersed for 10 s. in an IBA solution of 0, 2000, 4000 or 6000 mg L-1. At 30 and 60 days, the percentages of rooted cuttings; sprouted cuttings; and survival of cuttings; the number and length of sprouted and rooted cuttings were evaluated. Root cuttings treated with 6000 mg L-1 of IBA had the best response in terms of sprouting and rooting. Large root cuttings showed the highest percentage of sprouting (26%), the highest number of sprouts (0.30) and the longhest sprouts and roots (2.27 and 5.40 cm) at 60 days of evaluation. The third trial, root cuttings were classified according to the position in the root system as basal, medium and apical. Cutting measuring 1.0; 3.0 or 5.0 cm of length were immersed for 10 s. in an IBA solution of 6000 mg L-1. At 60 and 90 days, the percentages of rooted and sprouted cuttings; and survival; the number and length of sprouted and rooted cuttings were evaluated. Basal and medium cuttings had the best response in terms of sprouting and rooting. Root cuttings measuring 3.0 and 5.0 cm were better than those with 1.0 cm of length. In this study, we also carried out trials with minicuttings of louro-pardo. The first trial, ministumps from plantlets of asexual and seminal origin with six and 12 month-old were fertilized with different nutrient solutions. The production of minicuttings per ministump was evaluated after 30 and 60 days. Minicuttings from these ministumps were treated or not with 1000 mg L-1 of naphthalene acetic acid (NAA). At 30 days, the percentage of sprouting, rooting and survival; the number of sprouts; and the number and length of roots were evaluated. The second trial, minicuttings from ministumps of asexual and seminal origin were treated or not with 2000 mg L-1 of IBA. The same evaluations were done at 30 and 60 days. The concentration of the nutrient solution did not affect the production of minicuttings per ministumps. The concentrations of NAA and IBA did not affect minicutting rooting. Overall, ministumps from asexual origin showed adequate capability for vegetative propagation of louro-pardo. These ministumps have the highest production of minicutting associated with the highest rooting potential without any treatment.